The anatomy of the bond market turbulence of 1994 - Claudio E. V. Borio; Robert N. McCauley (Levy Economics Institute of Bard College, 1996)
This paper examines the sharp rise in bond yield volatility across the major bond markets in 1994. The analysis covers thirteen industrialised countries and is largely based on OTC data for implied bond yield volatility. We conclude that the market's own dynamics seem to provide a stronger explanation than variations in market participants' apprehensions about economic fundamentals. We identify three market dynamics: downward markets increase volatility; volatility spills over from certain markets onto others; and it can rise in the wake of substantial withdrawals of foreign investments. We find more limited evidence that monetary or fiscal policies accounted for the rise in volatility, at least by our measures. Moreover, changing expectations about growth and inflation, while perhaps at work in particular countries, do not offer much of a general explanation.
Keywords: 330